(untitled) (Annals of Medical Research, 2021)
Aim: Epilepsy is one of the most often neurological diseases in childhood. Children with epilepsy carry a risk of anxiety/depression. This situation has negative effects on the quality of life. This study is aimed to the evaluating of the quality of life in adolescents with epilepsy, to be determined how depression and anxiety affect the quality of life. Materials and Methods: This study was made 48 children with epilepsy, 48 healthy controls at 12-18 ages. This is descriptive epidemiological research. Data were added with a questionnaire composed of questions about socio-demographic characteristics, Pediatrics Quality of Life, Beck Anxiety, and Beck Depression Scales. Descriptive variables were shown noun (n) and percentage (%). Categorical variables were analyzed chi-square test. The normality of continuous variables was decided with Shapiro–Wilk test. Independent T-test and Mann-Whitney U Test were used in continuous variables. Results: The patient group’s 37.5%; the control group’s 54.2% are girls (p>0.05). The mean of ages (±SD) is 14.69(±1.84) in the group with epilepsy; 14.69(±1.72) in the control group. In children with epilepsy, 63.3% made monotherapy. The most used therapeutic agent is valproate. The group with epilepsy has a lower quality of life than the control (p=0.001). The group with epilepsy mean of Beck Anxiety Score is higher than the control (p=0.02). The mean of the Beck Depression Score of patients is higher than the control, but this was not significant (p=0.13). Conclusion: The quality of life score was lower in the patient-group that conforms to a lot of studies in the literature. Therefore child with epilepsy is at risk in terms of anxiety and depression.